Transfer of Aciclovir from Plasma to Human Breast Milk - Bork, Konrad; Kaiser, Thomas; Benes, Petr (Arzneimittelforschung, 2000)
Aciclovir (CAS 59277-89-3) is frequently used in herpes simplex virus diseases, but administration to lactating women occurs only rarely. Therefore, information about the pharmacokinetics of aciclovir in human breast milk is limited. The concentration in breast milk is 2 to 3 fold increased compared to plasma. The reason for this increase is unknown until now. An active transport mechanism has been assumed. The aim of this study was to prove whether the higher concentration of aciclovir in human breast milk is due to only a passive transfer.Two chambers separated by a semipermeable membrane were used. The first chamber contained plasma with aciclovir, the second chamber breast milk without aciclovir. The increase in aciclovir concentration in the second chamber was determined. The concentration of aciclovir in breast milk exceeded that of plasma after 2 h and reached a higher concentration. Thus, the higher aciclovir concentration in human breast milk is due to passive diffusion. No active transport mechanism is needed.
Keywords: Aciclovir, accumulation, concentration in breast milk, diffusion, milk/plasma ratio; CAS 59277-89-3